2023
DOI: 10.3390/ma16155441
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and Force Chain of Two-Dimensional Granular Systems under Continuous Loading

Abstract: A continuous loading experiment of a two-dimensional granular system was carried out and the experimental data were obtained by digital image correlation (DIC). The deformation field of the granular system and the changing laws of the deflection angle and coordination number of the granules on force chains with time were obtained. Based on the granule element method, the quantitative calculation of contact force was realized, and the internal force chains of the granular system were identified. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The deformations generated by the Terzaghi principle in a porous medium, in the context of tunnel works in soft rock and granular terrain, have been resolved with the use of FEM [11]. Chen et al [12] carried out a continuous loading experiment with a two-dimensional granular system and obtained the experimental data through digital image correlation (DIC). The experimental results indicated that the evolution of force chains was directly related to the number, geometric properties and permutation distribution of granules in direct contact with the external load.…”
Section: Introductionmentioning
confidence: 99%
“…The deformations generated by the Terzaghi principle in a porous medium, in the context of tunnel works in soft rock and granular terrain, have been resolved with the use of FEM [11]. Chen et al [12] carried out a continuous loading experiment with a two-dimensional granular system and obtained the experimental data through digital image correlation (DIC). The experimental results indicated that the evolution of force chains was directly related to the number, geometric properties and permutation distribution of granules in direct contact with the external load.…”
Section: Introductionmentioning
confidence: 99%